Blockchain Technology as a Factor of Global Modernization of International Processes of Customs Regulation. Application of the Digital System of Distributed Registers in the Customs Union of the Eurasian Economic Union Countries - V. A. Shamakhov; P. A. Koryagin; R. A. Kuntishev (Управленческое консультирование)
The article is devoted to the application of blockchain technology in international customs regulation processes, as well as the application of this technology in the framework of modernization of customs administration processes in the zone of the Customs Union of the EEU countries.